THE ANALYSIS OF SPIRITUAL INTELLIGENCE EFFECT AND EMOTIONAL INTELLIGENCE ON TEACHERS’ PERFORMANCE IN ISLAMIC BASED ELEMENTARY SCHOOL TEMBALANG, SEMARANG - Turmudhi, Anis; Kurdaningsih, Dian Marhaeni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research is based on several teachers qualification which are not in accordance with the rules of human being prepared to become a teacher.. This study focused in the influence of spiritual intelligence and emotional intelligence on teachers’ performance partially and simultaneously. Well, this present study is conducted in order to analyze and explain about the effect of two intelligence variables partially and simultaneously on the teachers’ performance of Islamic-based school in Tembalang, Semarang. This research method used quantitative analysis. The number of sample were 87 people, so the data collection used total sampling technique. The data collection technique used a questionnaire, and the data were tested using multiple regression analysis. The result showed that spiritual intelligence, emotional intelligence, and spiritual intelligence have positive and significant effect on teachers’ performance in Islamic-based elementary school in Tembalang, Semarang. However, the limitation of this present study are limited in time and minimalist funding. Keywords : spiritual intelligence, emotional intelligence, and teachers’ performance